Ginsenoside Rb1 ameliorates neutrophil extracellular traps-induced vascular endothelial damage by suppressing apoptosis (Bangladesh Journal of Pharmacology, 2024)
The study aims to investigate the effect of ginsenoside Rb1 on improving neutrophil extracellular traps-induced vascular endothelial damage. The CCK8 assay was used to evaluate the impact of ginsenoside Rb1 on cell activity. Flow cytometry was used to assess cell apoptosis. E-cadherin was used to determine the damage to endothelial cells, and caspase 3 was used to detect apoptosis-related proteins. Ginsenoside Rb1 (100 μmol/L) could significantly increase the cell viability (p